2011
DOI: 10.1002/ange.201003909
|View full text |Cite
|
Sign up to set email alerts
|

Expandierte Porphyrine: überraschende Strukturen, elektronische Eigenschaften und Reaktivitäten

Abstract: Die Chemie von expandierten Porphyrinen, den höheren Homologen der Porphyrine, wurde im Laufe der letzten drei Jahrzehnte ausgiebig untersucht. Expandierte Porphyrine weisen Strukturen, elektronische Eigenschaften, Reaktivitäten und ein Koordinationsverhalten auf, die sich gänzlich von denen der Porphyrine unterscheiden. Im Laufe dieser Untersuchungen wurde immer deutlicher, dass expandierte Porphyrine im Hinblick auf ihre Aromatizität und die Koordination an mehrere Metallionen oder als funktionelle Farbstoff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 222 publications
(42 citation statements)
references
References 324 publications
(176 reference statements)
0
41
0
Order By: Relevance
“…[1] The synthesis of many structural analogues, such as core-modified porphyrins, [2] N-confused porphyrins, [3] corroles, [4] porphycenes, [5] contracted porphyrins, [6] and expanded porphyrins, [7] have been investigated in conjunction with their diverse applications and the wider study of macroaromaticity. [1] The synthesis of many structural analogues, such as core-modified porphyrins, [2] N-confused porphyrins, [3] corroles, [4] porphycenes, [5] contracted porphyrins, [6] and expanded porphyrins, [7] have been investigated in conjunction with their diverse applications and the wider study of macroaromaticity.…”
Section: Dedicated To Professor Noboru Ono On the Occasion Of His 70tmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] The synthesis of many structural analogues, such as core-modified porphyrins, [2] N-confused porphyrins, [3] corroles, [4] porphycenes, [5] contracted porphyrins, [6] and expanded porphyrins, [7] have been investigated in conjunction with their diverse applications and the wider study of macroaromaticity. [1] The synthesis of many structural analogues, such as core-modified porphyrins, [2] N-confused porphyrins, [3] corroles, [4] porphycenes, [5] contracted porphyrins, [6] and expanded porphyrins, [7] have been investigated in conjunction with their diverse applications and the wider study of macroaromaticity.…”
Section: Dedicated To Professor Noboru Ono On the Occasion Of His 70tmentioning
confidence: 99%
“…Porphyrins have been the focus of intense research interest owing to their pivotal role in many important biochemical processes and their suitability for diverse applications in medicine, material science, and catalysis, based on the properties associated with their heteroaromatic 18p-electron conjugation systems. [1] The synthesis of many structural analogues, such as core-modified porphyrins, [2] N-confused porphyrins, [3] corroles, [4] porphycenes, [5] contracted porphyrins, [6] and expanded porphyrins, [7] have been investigated in conjunction with their diverse applications and the wider study of macroaromaticity. [8] Typically, synthetic work has focused on increasing or decreasing the number of the pyrrolic (or other heteocyclic) subunits within the macrocyclic ring and on varying the relative connectivity between the pyrrolic constituents or adjusting the number of bridging meso-carbon atoms.…”
Section: Dedicated To Professor Noboru Ono On the Occasion Of His 70tmentioning
confidence: 99%
“…Although the Heilbronner-Hückel theory was originally developed for monocyclic annulene systems, many examples of Mçbius aromatics have been found among porphyrin-like macrocycles. In our initial report, describing the first Mçbius aromatic porphyrinoid, [14] we showed that the A,D-di-p-benzi [28]hexaphyrin 3, a molecule combining structural features of expanded porphyrins [18,34,36,40,41] and benziporphyrins (1,2) [16,[42][43][44][45][46] (Scheme 1), acts as a dynamic aromaticity switch in solution. When dissolved in [D]chloroform, 3 a-H 2 exists in two forms which differ in the relative arrangement of p-phenylene units with respect to the macrocyclic core (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…This is because such materials possess interesting electronic, optical, biological, and structural properties. [19][20][21][22][23][24] Numerous studies have been carried out to modify this macrocyclic compounds, with the aim of modulating their nonlinear optical (NLO) performances, [25][26][27][28][29] because porphyrins are ideal building blocks for donor-acceptor-type molecular systems; porphyrins are suitable as electron donors for efficient electron transfer due to the small reorganization energies and this, together with their large p-conjugated systems, renders porphyrins promising candidates for NLO applications. [30][31][32] However, to the best of our knowledge, there is no report in the literature for the fabrication of MWCNT-porphyrin conjugates by using 1,3-dipolar cycloaddition reactions, [33][34][35] whereas the application of MWCNT-based nanohybrids is always hampered by their insolubility.…”
Section: Introductionmentioning
confidence: 99%